Safety and efficacy of transcatheter mitral valve repair in patients with COPD; results from real‐world cohort. Issue 1 (26th May 2022) - Alachkar, Mhd Nawar; Müller, Tobias; Alnaimi, Anas; Milzi, Andrea; Kneizeh, Kinan; Altiok, Ertunc; Schröder, Jörg; Reith, Sebastian; Marx, Nikolaus; Dreher, Michael; Almalla, Mohammad; Daher, Ayham
Abstract: Objective: To evaluate the safety and efficacy of transcatheter mitral valve repair (TMVR) in patients with chronic obstructive pulmonary disease (COPD). Background: Heart failure and COPD share many clinical features and commonly coexist. Data about the safety and efficacy of TMVR in patients with COPD is not conclusive. Methods: Three hundred and forty consecutive patients undergoing TMVR were retrospectively included. COPD diagnosis was based on pulmonary function tests (PFTs). Intra‐hospital, 30‐day‐ and 1‐year outcomes were compared between both groups. Results: Eighty‐two patients had COPD (24%). There was no difference in intra‐hospital mortality between patients with and without COPD (both 5%, p  = 0.95). Among patients who had a successful procedure and survived to discharge there was a trend toward more rehospitalization due to decompensated heart failure at 30‐day follow‐up in patients with COPD (12.9% vs. 6.8%, p  = 0.08) with no difference in mortality. At median follow‐up of 1 year, New York heart association (NYHA) category was comparable among both groups and there was no significant difference in rehospitalization (COPD: 29.9% vs. non‐COPD: 34%, p  = 0.5). There was a trend toward increased 1‐year mortality in COPD patients (31.2% vs. 20.6%, p  = 0.06). However, a composite endpoint of rehospitalization or death at 1 year did not differ between both groups (48% vs. 42.5%, p  = 0.4). Regression analysis showed no correlation between COPD severity and worse TMVR outcomes. Conclusions: COPD is highly prevalent among patients undergoing TMVR. However, TMVR seems to be safe and effective in COPD patients. COPD severity and PFT impairment alone should not be considered as a contraindication for TMVR.